Use and selection at two spatial scales by female moose (alces alces) across central British Columbia following a mountain pine beetle outbreak - Scheideman, Matthew (Author); Gillingham, Michael (Thesis advisor); Parker, Katherine (Committee member); Heard, Douglas (Committee member); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2018)
Moose are a keystone species and play a substantive role in predator-prey systems, nutrient cycling, and forest succession. Following a mountain pine beetle (MPB) spread across British Columbia, I quantified seasonal home-range selection, home-range size and daily movements, and within home-range selection of GPS-collared female moose in three study areas. I used case-matched logistic regressions with individual seasonal home-ranges, and mixed-effects logistic regressions for seasonal locations of female moose to determine habitat selection at two spatial scales. Individual variation was evident at both home-range and within-home-range scales. Female moose selected lodgepole pine-leading stands at both spatial scales regardless of mass die-off due to MPB. Clear-cuts following the MPB outbreak were avoided in drier locations, and trade-offs between cover and browse were evident where disturbance due to salvage logging was highest. My findings indicate that MPB salvage-logging reduced moose habitat, and thereby, influenced selection by female moose. female moose mountain pine beetle